BOVINE VIRAL DIARRHOEA AND PERSISTENTLY INFECTED ANIMALS IN DAIRY HERDS IN MAJES, AREQUIPA - Huamán G., Juan C. (2007)
The objective of this study was to determine the prevalence of bovine viral diarrhoea virus (BVDV) and persistently infected (PI) animals in dairy herds located in Majes, Arequipa, Peru. In the first phase, 204 bulk tank milk samples from to 204 herds were collected al the local commercial processing plant in Majes for detection of antibodies against BVDV by indirect ELISA test. In the second phase, 286 blood samples were collected from 57 strong positive (Optical Density [OD] ? 0.900) herds for the detection of antibodies against BVDV and in PI animals by the indirect and capture ELISAs respectively. In the third phase, blood samples were collected from all animals ranging from 6 to 24 months of age from three herds that had at least one PI animal. The prevalence of BVDV in the 204 herds was 98.0 ± 1.9% (200/204), and the level of antibodies ranged from 0.300 to 2.350 OD. The 47.2% (135/286) of serum samples had antibodies against BVDV, and within the negative samples, four (2.7%) animals from three herds were PI. Later on, additional PI animals were also detected in these three herds, and none of the six (4.0%) developed antibodies against BVDV. In conclusion, the results indicate that BVDV is widespread in dairy herds in Majes, the high level of antibodies suggests the presence of PI animals in the bovine population and finally, bulk tank milk samples are very useful for antibody detection from milking cows.